Teaching questioning and answering skills through Information-Gap Activities : a case study of Thai EFL students - Rongdara Rochanahasadin (Prince of Songkla University, 2012)
Thesis (M.A.TEIL., Teaching English as an International Language)--Prince of Songkla University, 2010